2018
DOI: 10.1016/j.jnoncrysol.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and time dependent structure of the molten Ni81P19 alloy by neutron diffraction

Abstract: The temperature and time dependent structure of molten NiP alloy of eutectic composition has been studied by neutron diffraction. Ni particles were found to exist in the melt at temperatures at least up to about 150 degrees above liquidus. The amount varies reversibly as temperature increases but decays slowly with time. Remarkably, particles still exist even after that the melt has been kept more than 30 hours at different temperatures in the molten state. The static structure factor and the pair distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…The CNA further indicated that significant fcc ordering persists as attested by the presence of about 10% 421 pairs, while the bcc ordering remains always small. Even though a fcc ordering is present in our structure, no pure Ni inclusions could be detected, as was hypothesized recently [40].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The CNA further indicated that significant fcc ordering persists as attested by the presence of about 10% 421 pairs, while the bcc ordering remains always small. Even though a fcc ordering is present in our structure, no pure Ni inclusions could be detected, as was hypothesized recently [40].…”
Section: Resultssupporting
confidence: 61%
“…In a first stage, the reliability of the EAM potential is tested against existing experimental data and ab initio calculations in the liquid and amorphous states. In figure 1 the total neutron scattering structure factor obtained by MD and AIMD in the liquid state at T = 1325 K is compared with experimental data of Dahlborg et al [40]. Both S N (q) simulation curves have been calculated using the ISAACS software [41].…”
Section: Resultsmentioning
confidence: 99%
“…However, the third coordination shell shifts bỹ 2.30%. It is noted that the position (6.5-6.7 Å) of the third coordination shell of the MG-subtracted pattern is similar to the position (~6.6 Å) of the third coordination shell of the Ni 81 P 19 metallic liquid 39 . To understand the significance of this increase, the peak positions for the third coordination shell of two representative metallic glass-forming liquids (MGFLs) and their glassy state counterparts: Zr 57 Nb 5 Al 10 Cu 15.4 Ni 12.6 (Vit 106) and Pd 43 Cu 27 Ni 10 P 20 were determined.…”
Section: Resultsmentioning
confidence: 59%